Personal transformations in the French theatrical text Robert Zuko's play as a model (Journal of the College of Basic Education, 2024)
The French theatrical text took on an important dimension in the world stage as one of the cultural, artistic and literary tributaries through what was produced of theatrical texts that took a different character in terms of writing as a style and technique and uniqueness in what was produced of works on the diversity of personalities and the accuracy of construction and treatments that were based on multiple transformations at the level The literary and cultural importance of the topic, the researcher chose this title for his research, which consisted of four chapters, according to what is practiced in scientific research in terms of the method of preparation, writing and literary treatment.The researcher found a group of agency generations:1- Contrasts, antagonisms, chaos, and their products in society’s societies cooperate as modern sources for constructing the event and the construction of the main characters, one of the methods and techniques used to construct events and their formations in writing French texts.2- Ways of expression prevail, in which instincts prevail over logic and thinking, and the copyright system operates as a confrontation with rejection and violent pressures that destroy the personality and throw it into complete chaos.3- The characters are drawn with internal psychological details that express the external and surrounding actions and events as a response to the rejection of the chaos and complexities dictated by modern societies, many of which take the behavior of their lives and actions.4- The characters in general, and the hero in particular, suffer from hesitation, psychological regression, lack of realization, and a distinction between life, murder, crime, and living love and hate through what embodiments in dealing between the characters represent the basis and the environment in which they live.5- The instinct constitutes the motive and the first and dominant factor in the process of writing and authoring to shape events and actions and give characters their definitions on the psychological and intellectual level.